IN SILICO STUDIES OF ATROPINE DERIVATIVES ON TO CBPF FOLLOWED BY GENOTOXICITY STUDIES - MANABENDRA MUKHOPADHYAY; RAMESH K.V. (International Journal of Pharma and Bio Sciences, 2016)
Computational studies were carried out with the aim of identifying a potential atropine derivative of choline binding protein F (PDB ID: 2X8O), other than atropine monohydrate sulphate. Among the various atropine derivatives, atropine-n-oxide HCL which got docked with an energy of -232.16 kcal mol-1., was considered for further analysis. Since the ligand was present in its unrefined form, it was subjected to the geometrical optimization technique as implemented in the GAUSSIAN software package. There was, however, no marked difference in the dock energy between unrefined and optimised atropine-n-oxide HCL,when docked onto the CBPF protein. As a part of genotoxocity study, which is yet to be conducted at a later stage, the identified potential ligand, atropine-n-oxide HCL, was docked to onto DNA to explore its affinity. The study showed that the ligand molecule got docked with an energy of -189.76 kcal mol-1 .